An Internet of Things‐enabled decision support system for circular economy business model. (5th April 2020) - Mboli, Julius Sechang; Thakker, Dhavalkumar; Mishra, Jyoti L.
Abstract: The traditional linear economy using a take‐make‐dispose model is resource intensive and has adverse environmental impacts. Circular economy (CE) which is regenerative and restorative by design is recommended as the business model for resource efficiency. While there is a need for businesses and organisations to switch from linear to CE, there are several challenges that needs addressing such as business models and the criticism of CE projects often being small scale. Technology can be an enabler toward scaling up CE; however, the prime challenge is to identify technologies that can allow predicting, tracking and proactively monitoring product's residual value to motivate businesses to pursue circularity decisions. In this paper, we propose an IoT‐enabled decision support system (DSS) for CE business model that effectively allows tracking, monitoring, and analysing products in real time with the focus on residual value. The business model is implemented using an ontological model. This model is complemented by a semantic decision support system. The semantic ontological model, first of its kind, is evaluated for technical compliance. We applied DSS and the ontological model in a real‐world use case and demonstrate viability and applicability of our approach.